PsycEXTRA Dataset 2004
DOI: 10.1037/e733232011-001
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Examination of Naturalistic Lane-Changes

Abstract: Michael Goodman was the NHTSA Task Order Manager for this project. 16. Abstract This research effort provided valuable insight into the nature and severity of lane changes in a naturalistic driving environment. Sixteen commuters who normally drove more than 25 miles (40 km) in each direction participated. The two research vehicles were a sedan and an SUV; each participant drove each vehicle for ten days. Data gathering was automatic, and no experimenter was present in the vehicle. There were 8,667 lane chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 37 publications
9
125
0
1
Order By: Relevance
“…The NHTSA Lane Change Study [3] and the Intelligent Vehicle Highway System review [41] both led to the hypothesis that measuring head dynamics may be enough to detect distinctive behavioral cues prior to a lane change. Having confirmed that hypothesis, it can be argued that the relative ease of capturing head motion information, compared with eye gaze in vehicles, outweighs the advantages of adding eye data to head, lane, and vehicle data.…”
Section: A Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The NHTSA Lane Change Study [3] and the Intelligent Vehicle Highway System review [41] both led to the hypothesis that measuring head dynamics may be enough to detect distinctive behavioral cues prior to a lane change. Having confirmed that hypothesis, it can be argued that the relative ease of capturing head motion information, compared with eye gaze in vehicles, outweighs the advantages of adding eye data to head, lane, and vehicle data.…”
Section: A Discussionmentioning
confidence: 99%
“…Correspondingly, during right lane changes, drivers looked at the right mirror with 36%-53% probability and the rearview mirror with 82%-92% probability. Moreover, the mirror glance duration before lane change maneuvers lasted, on average, 1.1 s, varying between 0.8 and 1.6 s [3]. Mourant and Donohue observed that lengthy blind spot checks occurred only in conjunction with lane-change maneuvers; in lane-keeping situations, no such checks were performed by the drivers [14].…”
Section: A Related Research In Lane Change Behavior Analysismentioning
confidence: 99%
See 3 more Smart Citations